The Influence of Career Development And Motivation on Employee Performance of Pt Kideco Jaya Agung - Mayawanti, Riani; Maulina, Anita (Publika : Jurnal Administrasi Publik, 2021)
This research examines to analyze the effect of career development and motivation partially and simultaneously on the employee performance of PT Kideco Jaya Agung. This research is based on empirical conditions such as limited promotional opportunities, economic downturns and global competition. Employees are performing their daily monotonous tasks from time to time, the employees sre not to supporting each other to accomplishing their tasks. Based on this background, this research is intended to analyze the effects of career development and motivation partially and simultaneously on the performance of employees of PT Kideco Jaya Agung. This research uses a quantitative-descriptive method to see how much the effects of the independent variable with a dependent variable represented by Variable Coefficient and the relationship between those both variables with Coefficient of Determination. Results of the research shows that variable x1 career development of Coefficient of Determination is 0.546, reflecting that the career development variable affects the performance and, the Effect is 54.6%. Career development obtains 4,650>2,110 t-value and the significance value is 0.000 <0.05, so it can be concluded that career development results in a significant positive effect on the performance. Results of the research shows that variable x2 motivation of Coefficient of Determination is 0.623, meaning that the motivation variable affects the performance and, the effect is 62.3%. Motivation obtains 5,457> 2,110 t-values and 0.000 <0.05 Significance Value, so it can be concluded that motivation results in significant posituve is effecting thr performance the performance. Career Development and Motivation obtained 0.713 Coefficient of Determination R square (r2), meaning that career development and motivation variables affect the performance and the effect is 71.3% and Significance Value is 0.000 <0.05, it can be concluded that career development and motivation simultaneously Effect or result in a joint effect on performance